2014
DOI: 10.1037/a0032572
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances predict later trauma-related distress: Cross-panel investigation amidst violent turmoil.

Abstract: Objective Sleep disturbances, including trouble falling and remaining asleep and recurrent nightmares, are symptoms of posttraumatic stress. A growing body of literature indicates that sleep disturbance may also convey vulnerability for the continuation of other symptoms of posttraumatic stress including fear, anxiety, and heightened arousal. However, longitudinal research, which could help understand how these relationships unfold over time, has been limited. Method The longitudinal relationships between sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Study 2 is based on the baseline Israeli data included in Study 1, along with data from a second survey conducted in Israel several months later, during Operation Protective Edge. Study 2 uses a longitudinal panel design ( Gerhart et al 2014 ) which tests for changes in attitudes over a period in which the country went from relative quiet to violent conflict, to evaluate whether the overall sense of threat varies within participants and between time points (though the number and status of asylum seekers remained fairly stable during that time).…”
Section: Empirical Strategymentioning
confidence: 99%
“…Study 2 is based on the baseline Israeli data included in Study 1, along with data from a second survey conducted in Israel several months later, during Operation Protective Edge. Study 2 uses a longitudinal panel design ( Gerhart et al 2014 ) which tests for changes in attitudes over a period in which the country went from relative quiet to violent conflict, to evaluate whether the overall sense of threat varies within participants and between time points (though the number and status of asylum seekers remained fairly stable during that time).…”
Section: Empirical Strategymentioning
confidence: 99%
“…Sleep disturbance itself may be a risk factor for development of PTSD following exposure to trauma (Bryant et al, 2010; Gehrman et al, 2013; Gerhart et al, 2014; Kobayashi & Mellman, 2012; Koffel et al, 2013; Spoormaker & Montgomery, 2008; Swinkels et al, 2013; Wright et al, 2011). A longitudinal investigation of sleep and trauma-related distress found that initial sleep problems predicted increased PTSD and depression at 6 month follow-up, whereas initial PTSD and depression did not predict increased sleep problems (Gerhart et al, 2014).…”
Section: Sleep Disturbances and Ptsdmentioning
confidence: 99%
“…A longitudinal investigation of sleep and trauma-related distress found that initial sleep problems predicted increased PTSD and depression at 6 month follow-up, whereas initial PTSD and depression did not predict increased sleep problems (Gerhart et al, 2014). A longer follow- up study similarly found that pre-deployment sleep complaints uniquely and incrementally predicted PTSD and depression up to two years after deployment, even after controlling for baseline psychiatric symptoms and negative emotionality characteristics (Koffel et al, 2013).…”
Section: Sleep Disturbances and Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of nightmares in posttraumatic stress disorder (PTSD) is 50-70% in several studies (see review by Wittmann, Schredl, & Kramer, 2007). Several studies document an association of PTSD severity and nightmare frequency (Blank, Kelly, Bootzin, & Haynes, 2009;Gerhart, Russ, Hall, & Canetti, 2014). Posttraumatic nightmares are a diagnostic criterion of PTSD according to ICD-10 (WHO, 2004) and DSM-5 (APA, 2013) and are considered to be emotionally the most intense type of dreaming (Levin & Nielsen, 2007).…”
Section: Introductionmentioning
confidence: 99%